(untitled) (Philadelphia, 1999)
Univ. Texas, Houston. Evidenced-based book with information on why and when to order neurologic diagnostic testing that is often not presented in general neurology texts. Presents the differential diagnosis of various disorders with the various testing available. Includes 18 new chapters and 13 previously published, newly revised articles.
Keywords: Nervous system,Hệ thần kinh,Neurologic examination,Khám bệnh thần kinh; Diseases,Bệnh,Chuẩn đoán